Sistem Informasi Manajamen Persediaan Barang pada Toko Bangunan UD. Alnas Menggunakan Eqonomic Order Quantity (EOQ) - Amiruddin Alnas; M. Fakhriza (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This study aims to optimize inventory management at UD. Alnas Building Store by implementing the Economic Order Quantity (EOQ) method. The main problem faced by this store is the uncertainty in the quantity of orders that will come, which can result in excess or shortage of inventory. One effective way to manage inventory is by using an inventory management information system. This article discusses the use of an inventory management information system in UD Alnas Building Store. This system is used to collect, store, and process information related to the store's inventory. Several features in the information system, such as recording stock items, monitoring sales, determining inventory needs, calculating Cost of Goods Sold (COGS), and generating reports, greatly assist in effective inventory management. Although it has some drawbacks, the use of inventory management information systems has helped UD Alnas Building Store managers in monitoring stock items, calculating, determining inventory needs, and generating accurate and timely reports.